Moderating effect of non-performing loans on bank capitalisation, liquidity risk and risk governance to bank performance in Sub-Saharan Africa - Adamu, Yahaya (2022)
The rate of banking failure across Sub-Saharan Africa is a great source of concern to all stakeholders in the industry, given the important role that banks play in promoting economic growth and development in the region. This study is motivated by the increase rate of poor banking performance despite all efforts by the regulators and management of banks to address it. The study aims to examine the moderating effect of non-performing loans on the impact of bank capitalization, liquidity risk and risk governance on bank performance with evidence from sub-Saharan Africa (SSA). A sample of 78 listed commercial banks across ten sub-Saharan Africa countries was drawn. The countries include, Nigeria, Ghana, South Africa, Kenya, Zambia, Tanzania, Mauritius, Malawi, Rwanda and Botswana that constitute the top performing economies within the region. The study covers a period of 9 years, from 2012 to 2020. The study employed a two-step system generalized method of moment as the method of inference. Findings from the study revealed a significant and positive relationship between bank capital, risk governance and bank performance, and a significant and negative relationship between liquidity risk, non-performing loans and bank performance. The moderation relationship is only significant for return on asset. The study therefore, makes the following recommendations; 1) a regular upward review of bank capital base, to be in line with global standard, 2) controlling the rate of non-performing loans and 3) increasing the number of risk experience members within the corporate governance structure of the banks.